Breastfeeding in women with diabetes: lower rates despite greater rewards. A population‐based study. Issue 9 (21st June 2013) - Finkelstein, S. A.; Keely, E.; Feig, D. S.; Tu, X.; Yasseen, A. S.; Walker, M.
Abstract Aims To explore intention to breastfeed and breastfeeding rates in hospital and on discharge across women with pre‐gestational or gestational diabetes mellitus, or no diabetes. Methods A retrospective cohort analysis was conducted using data from four Ontario hospitals. Women who delivered a viable infant between 1 April 2008 and 31 March 2010 were included in the study. Unadjusted and adjusted odds ratios were calculated for each outcome measure and were used to compare the breastfeeding rates among women with and without diabetes. Results After controlling for potential confounders, women with insulin‐treated diabetes were less likely to intend to breastfeed, when compared with women without diabetes (adjusted odds ratio 0.49, 95% CI 0.27–0.89). In hospital, women with insulin‐treated diabetes were least likely to breastfeed (odds ratio 0.42, 95% CI 0.26–0.67), followed by women with non‐insulin‐treated diabetes (odds ratio 0.50, 95% CI 0.26–0.96) and women with gestational diabetes (odds ratio 0.77, 95% CI 0.68–0.87) when compared with women without diabetes. On discharge, women with insulin‐treated diabetes were least likely to breastfeed (odds ratio 0.38, 95% CI 0.24–0.60), followed by women with gestational diabetes (odds ratio 0.75, 95% CI 0.66–0.85); rates of breastfeeding among women with non‐insulin‐treated diabetes were comparable on discharge with those of women without diabetes. Women seeking care from an antenatal provider other than a physician were 2–3 times more likely to breastfeed in hospital and on discharge. Conclusions Women with insulin‐treated diabetes had the poorest outcomes with respect to breastfeeding rates. Gestational and non‐insulin‐treated diabetes were associated with lower rates of breastfeeding in hospital, while gestational diabetes was additionally associated with lower breastfeeding rates on discharge.